Controlled‐atmosphere thermal demagnetization and paleointensity analyses of extraterrestrial rocks. (28th July 2014) - Suavet, Clément; Weiss, Benjamin P.; Grove, Timothy L.
Abstract We describe a system for conducting thermal demagnetization of extraterrestrial rocks in a controlled atmosphere appropriate for a wide range of oxygen fugacities within the stability domain of iron. Thermal demagnetization and Thellier‐Thellier paleointensity experiments on lunar basalt synthetic analogs show that the controlled atmosphere prevents oxidation of magnetic carriers. When combined with multidomain paleointensity techniques, this opens the possibility of highly accurate thermal demagnetization and paleointensity measurements on rocks from the Moon and asteroids.